Pengaruh Model Problem Based Learning Terhadap Hasil Belajar Pkn Siswa di Kelas V SD - Ningsih, Dian; Abidin, Zainal; Zuraida, Zuraida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to determine the significant effect on learning outcomes of student citizenship education using Problem Based Learning models. This type of research is a quasi-experimental research with non equivalent control group design. The sample in this study is Class V A and V B SDN 15 Ampang Gadang. Data collection techniques use tests. Hypothesis testing in this study uses the t-test formula. Based on the calculation of the t test (t-test) on the results of pretest tcount = -0.02238 and t table = 1.68 with a significant level of α = 0.05 of 1.68, then the tcount <ttabe posttest obtained the results of tcount = 2,745 and ttable = 1 , 68 at the significant level α = 0.05 at 1.68, then t count> t table. This means that there is a significant influence on student learning outcomes of Civics by using Problem Based Learning models.  Keyword : The Problem Based Learning Model, PKn, learning outcomes models